Next‐generation sequencing of residual cytologic fixative preserved DNA from pancreatic lesions: A pilot study. Issue 11 (29th June 2020) - Fulmer, Clifton G.; Park, Kyung; Dilcher, Thomas; Ho, Mai; Mirabelli, Susanna; Alperstein, Susan; Hissong, Erika M.; Pittman, Meredith; Siddiqui, Momin; Heymann, Jonas J.; Yantiss, Rhonda K.; Borczuk, Alain C.; et al.
Abstract : Background: Endoscopic ultrasound–guided fine needle aspiration (EUS‐FNA) is a sensitive and specific tool in the risk stratification of pancreatic lesions, including cysts. The sensitivity and specificity of EUS‐FNA has been shown to improve when cytology is combined with next‐generation sequencing (NGS). Ideally, fresh cyst fluid is used for NGS. In this pilot study, we explore the possibility of sequencing DNA derived from residual alcohol‐fixed pancreatic aspirates. Methods: Residual cytologic fixatives (n = 42) from 39 patients who underwent EUS‐FNA for pancreatic lesions were collected along with demographics, imaging, and laboratory studies. Samples were designated as nonneoplastic/nonmucinous benign (NB), mucinous cyst (MC), pancreatic ductal adenocarcinoma (PDAC), or well‐differentiated neuroendocrine tumor (NET) on the basis of cytopathologic evaluation and sequenced on the Oncomine platform (ThermoFisher Scientific, Waltham, Massachusetts). Results: Ten of 14 (71.4%) MCs exhibited clinically significant variants, including KRAS, GNAS, and TP53 . Ten of 15 (66.7%) PDACs had KRAS alterations, and 9 of 15 (60%) showed variants in TP53 . No variants were detected in any NETs. Only 1 of 9 (11.1%) NB aspirates showed variants in KRAS and MAP2K . Sequencing of formalin‐fixed, paraffin‐embedded tissue revealed variants identical to those detected in fixative‐derived DNA in 4 of 5 cases (80%). Conclusion: Residual DNA from alcohol‐fixed aspirates are an underutilized source for NGS. Sequencing residual fixative‐derived DNA has the potential to be integrated into the workup of pancreatic aspirates, possibly impacting management. Abstract : Residual cytologic fixatives from endoscopic ultrasound–guided fine‐needle aspiration of pancreatic lesions contain genetic material suitable for sequencing studies. Sequencing the genetic material preserved in these fixatives identifies the same variants as clinically validated sequencing studies performed on formalin‐fixed, paraffin‐embedded tissue.